Controversion about debriefing – research review - Urbaś, Paweł (Studia Psychologica: Theoria et praxis, 2004)
Preventive intervention after exposure to traumatic events is a subject of increasing interest among mental health professionals. Psychological debriefing (Critical Incident Stress Debriefing), which aims to reduce the risk of posttraumatic stress disorder and other psychopathological consequences of traumatic experience, is an example of such intervention. Even though, debriefing is widely used to prevent psychological trauma, it has come under considerable scrutiny over the last few years. Several studies have failed to document any effect of this method, while other documents significant positive effect. Most studies have serious methodological defects. In this article the author reveals the most important methodological problems such as: not complying with the Mischell’s model of debriefing, inadequate timing of intervention, using self- selection to the groups. It is concluded that the quality of conducting research at debriefing does not justify a discontinuation, but more support from controlled studies is required.